"Soviet suburbia". Issue 1 (April 2021) - Churakov, S K
Abstract: The article discusses the applicability of the term "suburbia" to the mass housing development in the USSR in the 60-70s of the XX century. For this, the main features of suburbia are formulated as a phenomenon manifested in different cultures. The first of them is an ideological model that determines the peculiarities of the lifestyle in the suburbs and acts as the main city-forming and formative factor. Being a special type of development of non-urban areas, suburbia is primarily determined by the type of the settlement, and not by the features of space-planning or urban planning solutions. From this point of view, suburbia is a mono-territory with a simplified approach to solving social, functional and planning tasks. Being the product of a design approach which does not rely on the historical tradition of the surrounding landscape development, suburbia is not a self-sufficient territorial entity, being a part of the city "orbit" as an element of the network structure with its own complex structure of economic, social, cultural and other kinds of connections. Replacing the suburbs or suburban settlements in the vicinity of the city, the suburbia loses their properties as elements of the settlement network. One of the main typological signs of suburbia is the massive, typical character of construction and urban planning solutions. At the same time, it is interpreted as the main place of residence of socially homogeneous population, the so-called "middle class", defined not by local traditions, but by the standards of the mass consumers. As a consequence of this approach, both in the American and Soviet versions of the suburbs of the 60-70s there are no complex zoning and functional density, no possibility of choice both in the typology of urban spaces and socially significant objects, no natural landscape and microlandscape identity.